Hubungan Bimbingan Belajar dengan Hasil Belajar Matematika Siswa Sekolah Dasar - Ayu Ristia; Dindin Ridwanudin (Elementar : Jurnal Pendidikan Dasar, 2022)
This study aims to determine whether there is a relationship between tutoring and student learning outcomes in mathematics in grade IV Elementary School, how much contribution is given and whether it has significance or not. This research was conducted in July-August at SDN Sumobito III. The research method used is correlational research with a quantitative approach. The sampling technique is purposive sampling. The research instrument used was a questionnaire and documentation of students' math scores. While the correlation technique used is the product moment. The results found in this study that there is a significant relationship between tutoring and student learning outcomes in mathematics. The results showed that the rcount or Pearson correlation was 0.923 and was included in the very strong category. While the value of the coefficient of determination in this study shows the figure of 85.2%. Thus, there is a very strong and significant relationship between tutoring and mathematics learning outcomes at SDN Sumobito III.Keywords: Tutoring, Mathematics Learning Outcomesutcomes